Digital Marketing Design Through Social Media For Abon Taminye Latuhalat Products In Tupa Hamlet Latuhalat Village, Ambon City - Meilissa Claudya Kalatty; Ambarwati Soetiksno; Julius Buyang; Stenly Ronaldo Titioka; Frangky Jansen Louth (Brilliant International Journal Of Management And Tourism, 2023)
This research aims to carry out digital marketing of Abon Taminye Latuhalat through social media to help UKM Merdeka Bergiat Group increase their product marketing potential. Small and Medium Enterprises or abbreviated UKM is a type of business that plays an important role in increasing the economic growth of a country. One of the SMEs in the city of Ambon, especially in the village of Latuhalat, is a fish floss business with the name "Abon Taminye Latuhalat". However, the problem faced by SMEs is in marketing and promoting their products. This research begins with observing the marketing of Abon Taminye Latuhalat products, by designing digital marketing using social media. The method at this writing uses the waterfall model or often called the linear sequential model or classic life flow, which is modified so that it can be applied. The waterfall model provides a sequential or sequential software life-flow approach starting from analysis, design, implementation, and testing. Based on these results, it can be concluded that the use of social media can be an initial alternative for the Merdeka Bergiat Group to market and promote Abon Taminye Latuhalat products. Sales using social media can be done anytime and anywhere. Therefore, in marketing Abon Taminye Latuhalat products, you must provide clear information such as important information about the product, price, and attractive promotions, so that social media account users when they see the post can receive interesting visual information and be willing to buy or even further explore the account from the post.